L'homosexualité masculine et les discours sur le sexe en contexte montréalais de la fin du XIXe siècle à la Révolution tranquille - Hurteau, Pierre (Histoire sociale / Social History, 1993)
La croyance populaire ainsi qu'une certaine théologie accordent souvent au discours religieux sur l'homosexualité une permanence doctrinale qu'il n'a pas. Les mythes populaires ont longtemps attribué la stigmatisation sociale de l'homosexualité au récit de Sodome. La critique historique du rapport entre religion et homosexualité permet cependant de mettre en évidence le caractère construit de ce discours et ses rapports avec le juridique et le médical. Le présent article veut établir de quelle manière ces discours ont pu s'élaborer au Québec, et particulièrement dans la région montréalaise, entre la fin du XIXe siècle et la Révolution tranquille. L'approche historique suggère une nouvelle herméneutique qui met en lumière les véritables impulsions qui sous-tendent le discours religieux sur l'homosexualité. Popular belief and certain types of theology often ascribe a continuity of doctrine to the religious discourse on homosexuality which, in fact, this discourse does not have. Popular myths have long attributed the social stigma of homosexuality to the story of Sodom. Historical criticism of the relationship between religion and homosexuality will bring to the fore the social construction of the religious discourse and its historical connections with the secular discourses of law and medicine. The following article will try to demonstrate how these discourses developed in Quebec, and particularly in the Montreal region, from the end of the nineteenth century to the Quiet Revolution. The historical approach taken here puts forward a new interpretation that brings to the light the real motivations that underlie the religious discourse on homosexuality.
Keywords: 1800-1899; 1900-1909; 1900-1999; 1910-1919; 1920-1929; 1930-1939; 1940-1949; 1950-1959; 1960-1969; LGBTQIA2+; Québec (Province); amériques; approches et analyses; canada; cours; discipline; discours dominant; discours religieux; his4860; histoire; histoire et politique; homophobie; homosexualité; hétérosexisme; montréal; patriarcat; premier cycle; périodes historiques; québec; religion; régions géographiques; révolution tranquille; sciences humaines; sexualité; soc2014; sofia; systèmes d'oppressions; thématiques

Only words - MacKinnon, Catharine A. (Harvard University Press, 1993)
When is rape not a crime? When it's pornography--or so First Amendment law seems to say: in film, a rape becomes "free speech." Pornography, Catharine MacKinnon contends, is neither speech nor free. Pornography, racial and sexual harassment, and hate speech are acts of intimidation, subordination, terrorism, and discrimination, and should be legally treated as such. Only Words is a powerful indictment of a legal system at odds with itself, its First Amendment promoting the very inequalities its Fourteenth Amendment is supposed to end. In the bold and compelling style that has made her one of our most provocative legal critics, MacKinnon depicts a society caught in a vicious hypocrisy. Words that offer bribes or fix prices or segregate facilities are treated by law as acts, but words and pictures that victimize and target on the basis of race and sex are not. Pornography--an act of sexual domination reproduced in the viewing--is protected by law in the name of "the free and open exchange of ideas." But the proper concern of law, MacKinnon says, is not what speech says, but what it does. What the "speech" of pornography and of racial and sexual harassment and hate propaganda does is promote and enact the power of one social group over another. Cutting with surgical deftness through cases of harassment in the workplace and on college campuses, through First Amendment cases involving Nazis, Klansmen, and pornographers, MacKinnon shows that as long as discriminatory practices are protected as free speech, equality will be only a word.
Keywords: 1900-1999; 1990-1999; amériques; approches et analyses; cours; discipline; droit; histoire et politique; patriarcat; premier cycle; périodes historiques; régions géographiques; science politique et droit; sciences humaines; sciences sociales; sex1911; sexisme; sexualité; sofia; systèmes d'oppressions; thématiques; violences; états-unis; études de genres

Pourquoi n'y-a-t-il pas eu de grands artistes femmes? - Nochlin, Linda (Femmes, art et pouvoir., 1993)
Keywords: approches et analyses; arts; cours; discipline; domination masculine; fem1000; histoire de l'art; histoire et politique; inégalités; patriarcat; premier cycle; systèmes d'oppressions; thématiques; théories féministes

Mais qu’est-ce qu’elles disent ? - Picq, Françoise (Libération des femmes: les années-mouvement, 1993)
Le 26 août 1970 à l'Arc de Triomphe, neuf femmes donnaient par une action symbolique le coup d'envoi d'un mouvement qui allait en une quinzaine d'années bouleverser profondément la société française.A partir de son expérience personnelle, de l'étude des écrits et des archives du Mouvement de libération des femmes, d'une enquête auprès des féministes de la première heure, Françoise Picq présente ici une histoire en trois temps : celui de la découverte, celui des contradictions, puis le temps de la réflexion et du bilan avec les années quatre-vingt.
Keywords: 1900-1999; 1970-1979; 1980-1989; approches et analyses; cours; discipline; droits des femmes*; europe; france; histoire et politique; inégalités; militance; mouvements de femmes*; patriarcat; postmodernisme; premier cycle; périodes historiques; régions géographiques; sciences humaines; soc1016; sociologie; systèmes d'oppressions; thématiques